Tenues huellas del Canzoniere en catalán - Arqués, Rossend (Cuadernos de Filología Italiana, 2005)
This article examines the main influence of Petrach’s Canzoniere in Catalan litterature. Given the lack of any complete translation of this work into Catalan, this article presents some of the best partial translations made during the XX Century and analyses Catalan Petrarchism present in the works of Pere Serafí (1505/1510-1567 and J.V. Foix (1984-).